Application of modified PROMETHEE method for coating quality enhancement in thin film deposition processes. Issue 3 (3rd July 2022) - Das, Partha Protim
ABSTRACT: Thin film coatings are extensively used to enhance the physical and chemical properties of various materials by depositing a thin layer of coatings of different materials onto various substrates. Several deposition processes are available which are widely adopted by many manufacturing industries to meet such demands. To exploit the fullest potential of those deposition processes, it is often advised to operate them with the optimal combination of process parameters. In this research, a modified PROMETHEE (preference ranking organisation method for enrichment evaluation) method as an effective multi-objective optimisation tool is applied for identifying the optimal parametric combinations of two thin film deposition processes: silicon carbonitride thin film coating using a thermal chemical vapour deposition process and zirconium-containing diamond-like-carbon thin film coating using an unbalanced magnetron sputtering process. The derived optimal parametric combinations are validated based on developed regression equations, which exhibit that the proposed approach can attain better response values as compared to other popular optimisation techniques. The analysis of variance results and the developed surface plots further illustrate the influence of various deposition parameters on coating quality.